Pengembangan LAMI Berbasis AR untuk Meningkatkan Literasi Digital Siswa pada Materi Lapisan Bumi Kelas 5 Sekolah Dasar - Rara Pramesthi Wandansari; Endang Sri Maruti; Sesaria Prima Yudhaningtyas (Mataram University, 2026)
This study was motivated by the low level of students’ digital literacy in learning the Earth’s layers. The purpose of this study was to determine the effectiveness of augmented reality media in improving the digital literacy of fifth-grade elementary school students. This study employed a research and development (R&D) approach using the ADDIE model. The participants consisted of 14 fifth-grade students. Data were collected through tests, questionnaires, and observations and were analyzed using a Likert scale. The results indicated that the use of augmented reality media was effective in improving students’ digital literacy, with a moderate level of improvement. Therefore, augmented reality media are considered feasible for use as instructional media in teaching the Earth’s layers.